We and the West - Demchenko, Alexander I. (Music Scholarship / Problemy Muzykal'noj Nauki, 2012)
In musicological editions from other countries related to art the apparent disproportion in relation to the amount of attention given to the Western world and to Russia displays the tendency of frequently ignoring what is genuinely noteworthy in the latter. The “universal responsiveness” of the Russian world, which in indispensible cases had approached the West for training in the sphere of the arts, has enriched its acquired knowledge and skills with inimitable personal qualities, spiritualizing them in a special way and elevating them to the heights of artistic perfection. One of the testimonies of this was the emergence in Russian music of the second half of the 19th century of the “Mighty Handful” composers and Tchaikovsky subsequently, in the first half of the 20th century of Rachmaninoff, Scriabin, Stravinsky, Prokofiev and Shostakovich, and at the second half of the 20th century – of Schnittke. Stravinsky represents an especially indicative symbol of “universality” of the Russian artistic genius. Keywords: The West and Russia, literature about art, achievements of Russian music